Know, teach and change. Approach to technologies in higher education - Martínez González, Ana Beatriz (2020)
In order to rethink the role of the teacher in terms of new educational scenarios, this paper analyzes some technological trends that are affecting higher education. This context acquires particular relevance due to the nature of the technological changes and their manifestation in the field of education. The methodology consisted of analyzing some of the main trends that are announced in various researches and recent reports on the presence of technologies in the educational field. As a result, some technological developments adopted in the context of higher education are presented, particularly the smart technologies that have been incorporated into the teaching-learning process.  Also, the skills demanded by professional and personal development in the face of new technological trends are considered. Finally, the role of the teacher is addressed in terms of the new scenarios posed by technology. The work concludes by pointing out that teacher training should be aimed at strengthening synthesizing, creative, respectful and connected thinking. It is about taking on the challenges of knowing, teaching and changing in the era of intelligent technologies.